Discourse analysis of religion and inter-communal conflicts and its causes in Nigeria - Ibenwa, Christopher N. (HTS teologiese studies, 2020)
The religious crisis in Nigeria dates back to the colonial era. The amalgamation of two distinct nationalities (Northern and Southern Nigeria) for the purpose of administrative convenience by the colonial government, irrespective of their cultural and educational differences, not only created a hitch in assimilation but also mistrust and bitter rivalry that has accentuated to conflict. In the same vein, most of the communal crises taking place today could be traced to colonial making as they created artificial boundaries that did not take cognisance of kith and kin, consanguinity and linguistic identity. It rather brazenly demarcated people to suit their exploitative governance. The above built-up grievances and tensions spark off a crisis at the slightest provocation or misunderstanding. The objectives of the study are as follows: (1) to identify the factors responsible for the crises, (2) to trace and analyse the antecedents of the crises, and finally (3) to proffer solutions to this seemingly intractable national problem. The methodology adopted for the study is the qualitative phenomenological approach, whereby data were collected from secondary sources and treated analytically. The work found that religion and inter-communal conflict have hindered sustainable development, taking a large toll of lives and property amongst others.